The Three Taverns: A Book of Poems - Robinson, Edwin Arlington, 1869-1935 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Three Taverns: A Book of Poems" by Edwin Arlington Robinson is a collection of poems written during the early 20th century. The work delves into the complexities of human emotions and experiences, weaving themes of memory, loss, and the passage of time throughout the pieces. It touches on various aspects of life, reflecting on social interactions, personal struggles, and deeper philosophical inquiries. The opening of this poetry collection sets a reflective tone, exploring existential themes through vivid imagery and contemplative verses. The first poem, "The Valley of the Shadow," introduces the reader to a haunting landscape of human experience, encapsulating feelings of isolation and the search for meaning in life. Robinson uses metaphorical expressions to depict the struggles of individuals who grapple with their identities and pasts while navigating their present realities. The verses paint a vivid picture of the human condition, leaving the reader to ponder the enduring nature of hope and despair. Overall, the beginning of this collection invites readers into a world rich with emotional depth and introspection. (This is an automatically generated summary.)
Release date is 1997-09-01
Produced by Alan R. Light. HTML version by Al Haines.
Keywords: American poetry; Lyric poetry